Strength of masonry mortars under field exposure conditions - (:unkn) unknown (American Ceramic Soc, Westerville, OH, United States, 1999)
Strength development in cement, low-lime and high-lime masonry mortars under outdoors field exposure conditions is investigated and correlated to the results of laboratory-controlled various temperature-humidity exposure tests reported earlier. Results obtained from specimens made in January and June, and exposed outdoors for periods up to one year, in Jeddah, Saudi Arabia are in many cases comparable with 20-35 °C and occasionally with 35-50 °C controlled environment tests. Both laboratory-controlled and field-exposure tests are widely used because they both have merits; it is an important observation that their results can be compared with each other.